Satisfaction of Pregnant Women Toward Integrated Antenatal Care Service in Senduro Health Center, Lumajang in Decreasing MMR and IMR Based on Pregnant Mother’s Characteristics - Aini Hidayati; Al Munawir; Ancah Caesarina Novi Marchianti (Aloha International Journal of Health Advancement (AIJHA), 2020)
Maternal Mortality Rate becomes a global issue because it is an important indicator in determining public health degree, so each country has responsibility to avoid maternal death. An effort in accelerating the decrease of MMR with pregnancy checkup program is well known as Integrated ANC service program. Integrated ANC service is a comprehensive and quality antenatal provided to all pregnant mothers temporally during pregnancy. This research was aimed to analyze the satisfaction level on pregnant mothers on Integration of ANC service decreasing MMR and IMR based on characteristic of pregnant mothers in Senduro Health Center of Lumajang Regency on 2019. Type of this research was descriptive analysis using quantitative approach. Questionnaire about satisfaction level of ANC service in Senduro Health Center of Lumajang Regency on September to October in 2019 was applied. It also took 670 populations of pregnant mothers coming to Senduro Health Center of Lumajang Regency. Samples were taken by using systematic random sampling. Samples taken were 109 respondents based on specified criteria. Data collection results were processed by employing Chi Square statistical test with a significant level of 0.05. The result of this research showed that most patients about 58 pregnant mothers (53.2%) were quite satisfied, 45 pregnant mothers or about 41.3% were very satisfied and 6 pregnant mothers or about 5.4% were still unsatisfied on the service provided. It could be concluded that 53.2% patients were quite satisfied to the Integrated ANC service in Senduro Health Center of Lumajang Regency. Keywords: satisfaction; pregnant mother; ANC service